1961
DOI: 10.1161/01.cir.23.4.550
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Aschoff Bodies in Atrial Appendages of Patients with Mitral Stenosis

Abstract: Three hundred and sixteen biopsies of atrial appendages obtained at mitral valvotomy were studied histologically. They were divided into those with Aschoff bodies (41 per cent), those with nonspecific granulomas (23 per cent), and those without either lesion. These findings were compared with those of previous investigators. A study of 24 hearts with mitral stenosis and survey of the literature showed that Aschoff bodies in the left atrial appendage are usually accompanied by similar lesions in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1962
1962
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Several studies have demonstrated the occurrence of ultrastructural changes resulting in fibrosis in the atria of patients with RHD . A pathognomonic feature of rheumatic carditis is the Aschoff bodies . Such inflammatory tissue can arise during an acute episode of carditis and remain immunologically active for years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the occurrence of ultrastructural changes resulting in fibrosis in the atria of patients with RHD . A pathognomonic feature of rheumatic carditis is the Aschoff bodies . Such inflammatory tissue can arise during an acute episode of carditis and remain immunologically active for years.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 A pathognomonic feature of rheumatic carditis is the Aschoff bodies. 19 Such inflammatory tissue can arise during an acute episode of carditis and remain immunologically active for years. They have been associated with the local release of a variety of cytokines, including many that are implicated in fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated both structural and electrical biatrial abnormalities in these cases. These patients are reported to have direct myocardial fibrosis and inflammation in both the right and LA related to carditis apart from hemodynamic consequences from valvular disease 34–38 . Thus, we cannot manage these cases with mere PVI as we do in NVAF.…”
Section: Discussionmentioning
confidence: 99%
“… n/a, not available . a There were missing data on age in 2 patients in the paper by Decker et al ( 6 ) and in 21 patients in the paper by Ruebner et al ( 19 ) . …”
Section: Discussionmentioning
confidence: 99%